Christian wisdom: desiring God and learning in love - Ford, David (Cambridge studies in Christian doctrine, 2007)
What is Christian wisdom for living in the twenty-first century? Where is it to be found? How can it be learnt? In the midst of diverse religions and worldviews and the demands and complexities of our world, David Ford explores a Christian way of uniting love of wisdom with wisdom in love. Core elements are the 'discernment of cries', the love of God for God's sake, interpretation of scripture, and the shaping of desire in faith. Case studies deal with inter-faith wisdom among Jews, Christians and Muslims, universities as centres of wisdom as well as knowledge and know-how and the challenge of learning disabilities. Throughout, there is an attempt to do justice to the premodern, modern and postmodern while grappling with scripture, tradition and the cries of the world today. Ford opens up the rich resources of Christianity in engaging with the issues and urgencies of contemporary life.